Inspiration For Carving Gorga Adop-Adop In Technology-Based Pop Batik On Ready-To-Wear Clothing - Apriyani, Yayuk (Institut Seni Indonesia Yogyakarta, 2022)
Technology-based pop batik is a popular style of contemporary batik with part of the production process using technology without leaving the rules of batik. Technology is the lifestyle of today's younger generation, which causes the traditional batik handicraft industry not to become a job opportunity that is in demand by the younger generation. Batik craftsmen are now living with the elderly, and it is complicated to regenerate in the field of batik crafts. There needs to be an adjustment between the development of the era and traditional culture so that the younger generation is interested in developing batik. The adjustment step that can be done is to process batik based on technology without leaving the rules of batik itself. This research uses the approach of textile design creation methods, aesthetic practices and semiotics. This research discusses how the implementation of Adop-Adop Gorga carving is an inspiration for technology-based pop batik motifs. Research shows that the technology-based batik process can be a solution to the complex problem of regeneration of traditional batik craftsmen and Adop-Adop Gorga carving as inspiration for pop batik motifs with a technology-based batik process is a uniqueness that distinguishes it from other contemporary batik motifs.